Safety Considerations in the Development of Hippo Pathway Inhibitors in Cancers - Kakiuchi-Kiyota, Satoko; Schutten, Melissa M.; Zhong, Yu; Crawford, James J.; Dey, Anwesha (Frontiers in Cell and Developmental Biology, 2019)
The Hippo pathway is a critical regulator of cell and organ growth and has emerged as a target for therapeutic intervention in cancers. Its signaling is thought to play an important role in various physiological processes including homeostasis and tissue regeneration. To date there has been limited information about potential pharmacology-related (on-target) safety liabilities of Hippo pathway inhibitors in the context of cancer indications. Herein, we review data from human genetic disorders and genetically engineered rodent models to gain insight into safety liabilities that may emerge from the inhibition of Hippo pathway. Germline systemic deletion of murine Hippo pathway effectors (Yap, Taz, and Teads) resulted in embryonic lethality or developmental phenotypes. Mouse models with tissue-specific deletion (or mutant overexpression) of the key effectors in Hippo pathways have indicated that, at least in some tissues, Hippo signaling may be dispensable for physiological homeostasis; and appears to be critical for regeneration upon tissue damage, indicating that patients with underlying comorbidities and/or insults caused by therapeutic agents and/or comedications may have a higher risk. Caution should be taken in interpreting phenotypes from tissue-specific transgenic animal models since some tissue-specific promoters are turned on during development. In addition, therapeutic agents may result in systemic effects not well-predicted by animal models with tissue-specific gene deletion. Therefore, the development of models that allows for systemic deletion of Yap and/or Taz in adult animals will be key in evaluating the potential safety liabilities of Hippo pathway modulation. In this review, we focus on potential challenges and strategies for targeting the Hippo pathway in cancers.